Phenomenological study of search of heavy neutrinos, with displaced vertices and vector Boson fusion (2017)
"The Standard Model is the theory that describes the fundamental particles and their interactions. This theory is incomplete because it does not explain various phenomena observed experimentally in particle physics. For example, the Standard Model predicts that neutrinos are massless and does not explain the observation of only left-handed neutrinos. The simplest extension of the standard model that can explain these phenomena is the Seesaw Mechanism, which proposes the existence of heavy right-handed neutrinos. In this project, we studied the possibility of detecting these particles in the CMS detector. In order to do this, the computational programs MadGraph, Pythia, Delphes and ROOT are used to simulate the signal and backgrounds." -- Tomado del Formato de Documento de Grado.